The Effect of Variation of Species and Types of Sugar on the Quality of Fruitghurt from the Mesocarp Layer of Watermelon (Citrullus lanatus) Based on Organoleptic Tests - Lestari Nova Dwi; Handayani Nursasi (BIO Web of Conferences)
Utilizing the mesocarp layer of watermelon to make processed fruitghurt is a way to reduce watermelon rind contamination and food diversification efforts. Fruitghurt is an innovative product development from yogurt added with fruit juice, including the rind. The study was conducted to determine the influence of variations in watermelon species and types of sugars on the quality of watermelon mesocarp fruitghurt based on organoleptic tests through aroma, texture, and taste. This study included an experimental study with a Completely Randomized Design (CRD), with 4 treatments (a combination of red watermelon mesocarp+granulated sugar, red watermelon mesocarp+palm sugar, yellow watermelon mesocarp+granulated sugar, yellow watermelon mesocarp+palm sugar and control) and carried out 4 repetitions. The results showed that the combination of red watermelon mesocarp treatment and granulated sugar had a significant effect and was significantly different from the control treatment and other treatments.